Leading during change: the effects of leader behavior on sickness absence in a Norwegian health trust - Bernstrøm Vilde Hoff; Kjekshus Lars Erik (BMC Public Health, 2012)
Abstract Background Organizational change often leads to negative employee outcomes such as increased absence. Because change is also often inevitable, it is important to know how these negative outcomes could be reduced. This study investigates how the line manager’s behavior relates to sickness absence in a Norwegian health trust during major restructuring. Methods Leader behavior was measured by questionnaire, where employees assessed their line manager’s behavior (N = 1008; response rate 40%). Data on sickness absence were provided at department level (N = 35) and were measured at two times. Analyses were primarily conducted using linear regression; leader behavior was aggregated and weighted by department size. Results The results show a relationship between several leader behaviors and sickness absence. The line managers’ display of loyalty to their superiors was related to higher sickness absence; whereas task monitoring was related to lower absence. Social support was related to higher sickness absence. However, the effect of social support was no longer significant when the line manager also displayed high levels of problem confrontation. Conclusions The findings clearly support the line manager’s importance for employee sickness absence during organizational change. We conclude that more awareness concerning the manager’s role in change processes is needed.